2019
DOI: 10.1021/acsami.9b04098
|View full text |Cite
|
Sign up to set email alerts
|

Photostable Iridium(III)–Cyanine Complex Nanoparticles for Photoacoustic Imaging Guided Near-Infrared Photodynamic Therapy in Vivo

Abstract: The iridium­(III)–cyanine complex (IrCy) was fabricated by conjugating an iridium­(III) complex to a cyanine dye with an intense near-infrared (NIR) absorption. IrCy complex nanoparticles (NPs) with high water solubility and photostability were prepared by a solvent evaporation-induced self-assembly strategy. Considering their effective photacoustic (PA) imaging and generation of 1O2 property with 808 nm laser irradiation in aqueous solution, PA imaging guided NIR-driven photodynamic therapy in vivo was effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Despite the demonstrated photoactivity of the cyanine to treat and reduce tumors [61,62,105,106], a single phototherapy approach seems to limit the in vivo therapeutic efficacy, particularly to treat extended and deep tumors [76,[107][108][109]. To overcome these drawbacks, a promising strategy could be the combination of different phototherapeutic approaches such as photodynamic and photothermal therapies.…”
Section: In Vivo Pdt Studies Of Cyanine Dyesmentioning
confidence: 99%
“…Despite the demonstrated photoactivity of the cyanine to treat and reduce tumors [61,62,105,106], a single phototherapy approach seems to limit the in vivo therapeutic efficacy, particularly to treat extended and deep tumors [76,[107][108][109]. To overcome these drawbacks, a promising strategy could be the combination of different phototherapeutic approaches such as photodynamic and photothermal therapies.…”
Section: In Vivo Pdt Studies Of Cyanine Dyesmentioning
confidence: 99%
“…A solvent evaporation‐induced self‐assembly approach made Iridium Cyanine (IrCy) complex NPs with good water solubility and photostability [92] . TEM results showed that the size of the micellar structure reduced from 76 to 34 nm as the PEG length was increased.…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…[40] Photoacoustic (PA) imaging combined with NIR excitation with thermal-ultrasonic detection can provide deeper tissue penetration, compared with fluorescence imaging. [41] The activatable PA imaging probes with biomarker-triggered signals can be used for in vivo imaging of biological biomarkers and metabolites at the molecular level, which is of great significance for real-time in vivo monitoring of immune response. [42] Zhang et al [35] developed a semiconducting polymer nanoprobe (SPNP) that detected the granzyme B released after CTLs immune activation by changing the near-infrared fluorescence (NIRF) and PA signal.…”
Section: Granzyme Bmentioning
confidence: 99%
“…Due to high photon absorption and scattering, it is difficult for fluorescent probes to penetrate deeper tissues [40] . Photoacoustic (PA) imaging combined with NIR excitation with thermal‐ultrasonic detection can provide deeper tissue penetration, compared with fluorescence imaging [41] . The activatable PA imaging probes with biomarker‐triggered signals can be used for in vivo imaging of biological biomarkers and metabolites at the molecular level, which is of great significance for real‐time in vivo monitoring of immune response [42] .…”
Section: Granzyme Bmentioning
confidence: 99%